PENGEDAR NARKOBA DALAM HUKUM ISLAM - Syafar Alim Siregar (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2019)
Online media coverage in 2018 entitled Why Drug Floods in Indonesia Continue to Increase ?. Reported that BNN as a government agency dealing with drug trafficking in Indonesia has succeeded in uncovering and confiscating 2 tons of drugs in the Riau Archipelago. The figure according to BNN is a small number, because the 2 tons is only a 10% figure of the number of drugs that have made it into Indonesian territory. The rise of drug trafficking in Indonesia the author tries to analyze drug dealers from the lens of Islamic law